PENINGKATAN AKTIVITAS BELAJAR PESERTA DIDIK PEMBELAJARAN IPS TIPE PEMBAGIAN PRESTASI TIM SISWA DI SD - Sorna, Sorna; Marzuki, Marzuki; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to "improve the learning activities of students using the type of learning as a team in the learning of social science in third grade public elementary school 05 Lamat Payang". The method used is descriptive method with the form of classroom action research. The procedure in this study consists of planning, implementing, observing and reflecting. Data collection techniques used are direct observation techniques and document scrutiny techniques. Data collection tools used are in the form of observation sheets and document observation sheets. Data collection techniques used are direct observation and measurement techniques by means of data collection, namely Student Activity Sheet. This research was carried out in three cycles. The results of the study were obtained. The ability of teachers to plan learning has increased from cycle I with an average score of 3.16 to 3.33 in the second cycle to 3.56 in cycle III. The ability of teachers to carry out learning has increased from cycle I which has an average value of 3.34 to 3.45 in cycle II, to 3.85 in cycle III. Increased learning activities of students in the learning of Social Sciences using the type of learning as a team on average students in the first cycle were 53.49 in the second cycle of 67.78 and in the third cycle was 80.35. Based on this data analysis, it can be concluded that the type of learning as a team can be used to increase the activity of third grade students of Lamat Payang 05 elementary school.Â Keywords: Student Activity, Learning Type as Team and Social Sciences